Emergence of Colistin Resistance Gene mcr-8 and Its Variant in Raoultella ornithinolytica - Wang, Xiaoming; Wang, Yao; Zhou, Ying; Wang, Zheng; Wang, Yang; Zhang, Suxia; Shen, Zhangqi (Frontiers in Microbiology, 2019)
Recently, a novel mobile colistin resistance gene, mcr-8, was identified in Klebsiella pneumoniae. Here, we report the identification of mcr-8 and its variant, mcr-8.4, in Raoultella ornithinolytica isolates which also belong to Enterobacteriaceae family. The mcr-8 gene was located on transferrable plasmids with difference sizes. Notably, the transferability of mcr-8-carrying plasmids was enhanced once they entered into E. coli hosts and multiple β-lactamase genes could co-transfer with mcr-8. These findings expand our knowledge of mcr-8-carrying bacterial species.